PENGEMBANGAN MEDIA ROULETTE BINGO DALAM PEMBELAJARAN BAHASA INDONESIA SEKOLAH DASAR - Kusumaningtyas, Windy Cahyani; Danawati, Murtyas Galuh; Ulum, Bahrul (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The results of the needs analysis of class IV at SDN 3 Tugu Tulungagung showed that there were students who had difficulty in understanding the teacher's explanation in interpreting sentences in Indonesian reading texts and the minimal use of learning media caused students to tend to be passive. Based on these results, the researcher developed Roulette Bingo media which aims to support learning with a fun and active atmosphere and help students understand the material. This study uses the ADDIE model. Data collection techniques used were observation, interviews, questionnaires, and documentation. Quantitative data were analyzed descriptively and qualitative data were analyzed using a Likert scale. The results obtained from the development of Roulette Bingo Media in Indonesian language learning for class IV related to the material on main ideas and supporting ideas based on the assessment determined by the material expert obtained a percentage of 87.5%, and media expert validation of 92.5% with the category "Very Appropriate". Meanwhile, the response from the teacher to the Roulette Bingo media received a percentage of 100% and the response from students was 94.4% with the category "Very Good". The results of this study indicate that the development of the Roulette Bingo media can be used as a tool to support learning materials that are fun and make students more active and motivated to follow the learning, but still has a drawback, namely the arrow on the Roulette is a little difficult to rotate, it is hoped that the Roulette can be rotated easily and practically in its use and adjusted to the needs of students.